Basic business finance : text and cases - Hunt, Pearson; Williams, Charles Marvin; Donaldson, Gordon (Homewood, Ill. : R. D. Irwin, 1971)
This book serve as an introduction to the field of corporation finance, it is more properly named "basic" because it holds steadily to its focus on the decision-making financial officer within the firm.
Includes bibliographical references and index.
hza 06/08/2018
Loans
Keywords: Finance